UNVEILING THE DYNAMICS OF WORD COMBINATIONS AND THEIR VARIED TYPES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article offers a comprehensive exploration of word  combinations, delineating their diverse structures and types within language. It examines  various categories, including collocations, phrasal verbs, idioms, compound words, and  proverbs, elucidating their unique characteristics and roles in linguistic communication. The annotation emphasizes the significance of word combinations as integral  components that enrich language expression, providing depth and versatility in  conveying nuanced meanings. It underscores the importance of understanding these  structures for enhancing language proficiency and navigating the intricacies of idiomatic  language use. Overall, the article serves as a valuable guide, unraveling the complexities of word combinations and their multifaceted contributions to linguistic fluency and  comprehension